Competence Approach and Basic Definitions of Informative Process of the Future Translators Training - Yevhen Dolyns’kyi (Pedagogical Discourse, 2013)
The article deals with the importance of implementing the competence approach in training of future translators. The basic definitions of the process of information and computer training of the future translators are characterized. Due to computerization of education the importance of formation the informative competence is very high. Informatization is the decisive factor in achieving the main goals of modern education. The content, essence, definitions of invormative competence are revealed, also examined main concepts of research. The basic tools of computer training are determined. The possible ways of using electronic learning in the process of studing foreign languages are described.